О комплексе жилых построек эпохи Золотой Орды на Царином городище - Швецов, М.Л. (Степи Европы в эпоху средневековья, 2012)
The excavated site P-1T is located in the northwestern area of a hillfort near Maiaki village. During the excavation works the objects found level-by-level were compared with the finds from the closed complexes. Having examined the objects found, the author distinguished two constructive horizons and four periods of existence of the hillfort dated back to the Golden Horde time. The preliminary analysis of the finds from the excavated site of the hillfort demonstrates characteristic features of the inhabited and household constructions typical of the Golden Horde time towns. The second period seems to correspond to the period of prosperity of the hillfort in the Golden Horde time. The fact that there was a sufa with a little hearth and tandyr in dwelling 2 (the third period) indicates significant Oriental influence. The absence of public or administrative constructions at the site can be explained not only by incomplete investigation of the site, but also by the existence of “a well known Muslim centre near Raigorodok village of Izum district’' next to it (at the distance of several kilometers) discovered by V.F.Spesivtsev in the late 19th century.